Model of Educational Work on Career Guidance in the System of Secondary Vocational Education - Goncharenko, Olga Nikolaevna (2021)
Youth is a dynamically developing social group that actively participates in the reproduction process of the social and professional structure of society. The complication of production processes and rapid scientific and technological progress increase the importance of this social group in Russian society. This scientific article attempts to study the level of implementation of career guidance in the system of educational work of an educational institution of secondary professional level. Using a system-synergetic approach and various methods of scientific research, the authors revealed not only the state of the problem under consideration but also determined the relevance of such research in contemporary conditions. Based on the obtained data, a theoretical universal model of educational work has been developed, which assumes the formation of value orientations among young people in the course of its implementation. The student professional development model concerning the educational activities of the College consists of three interrelated units: target, substantive-operational, and evaluation- performance blocks. The model provides self-development of the individual through the cardinal renewal of all the above-mentioned components, and the formation of general cultural competencies. The main advantage of the created model is the development of complete professionalism through the implementation of career growth mechanisms in students, as well as the orientation of young people to actively search for innovative conditions for professional self-actualization and civic-mindedness.